Cyient: enabling innovation through idea tree initiative. Issue 3 (14th July 2020) - Joseph, Nidheesh; Makhecha, Upam Pushpak
Abstract : Learning outcomes: The case would help students to learn the concept of high involvement innovation activity and how to apply it in large service organizations to increase innovation involvement. The case will help the students to reflect on the significance of organizing structure and culture of an organization for enabling innovation and innovation process models. The case would further help the students to develop the skill to plan and implement simple, innovative innovation process models which will increase the ideation capabilities of the organization. The students will also be able to understand the role of informal learning in innovation and how to facilitate it. Case overview/synopsis: Cyient – a global services firm – had always focused on innovation as a key strategic capability winning various annual client awards for over a decade. However, in 2012, Cyient missed the innovation awards which led to the introduction of Idea Tree initiative in Aerospace & Defense (AED) business unit of Cyient. Cyient was able to co-create patents and offer cost savings to its clients through the Idea Tree initiative. This cost-effective and unique initiative resulted in re-organizing the structure (from formal to a quasi-formal), culture (open to new ideas, mistakes and failures) and process (stage-gate) inside Cyient AED business unit. However, Idea Tree also suffers from challenges such as lack of a digital format, lack of corporate presence across Cyient and its highly informal nature. In this context, the CEO wants to review the Idea Tree initiative to decide on its future in Cyient. Complexity academic level: The case is suitable for teaching multiple facets of innovation for MBA and Executive MBA classes in core Strategy, Managing Organizations and Entrepreneurship and for elective courses such as Innovation Management, Organizing for Innovation or HRM for Innovation. The case is suitable for both fresher and experienced participants. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 6: Human Resource Management.